Anlotinib for Patients With Metastatic Renal Cell Carcinoma Previously Treated With One Vascular Endothelial Growth Factor Receptor-Tyrosine Kinase Inhibitor: A Phase 2 Trial - Ma, Jianhui; Song, Yan; Shou, Jianzhong; Bai, Yuxian; Li, Hanzhong; Xie, Xiaodong; Luo, Hong; Ren, Xiubao; Liu, Jiyan; Ye, Dingwei; Bai, Xianzhong; Fu, Cheng; et al. (Frontiers in Oncology, 2020)
Introduction: Sequential therapy with vascular endothelial growth factor receptor-tyrosine kinase inhibitors (VEGFR-TKIs) is effective in some patients with metastatic renal cell carcinoma (mRCC) progressed from or were intolerant to a prior TKIs. Anlotinib is a multi-kinase inhibitor targeting VEGFR1/2/3, PDGFR and FGFR, which has demonstrated efficacy and safety in first-line treatment of mRCC. This study assessed the potential of anloitnib as second-line treatment for patients with mRCC after prior one VEGFR-TKI. Methods: This is a single-arm, open-label, phase 2 study. Patients progressed after or were intolerant to sorafenib or sunitinib were enrolled. Anlotinib was administrated orally 12 mg once daily for 14 days every 3 weeks. The primary endpoint was progression-free survival (PFS). Secondary endpoints included overall survival (OS), objective response rate (ORR), safety and quality of life (QoL). Results: Forty three patients were enrolled and 42 received anlotinib, of whom 32 progressed after and 10 were intolerant to sorafenib or sunitinib. Median PFS were 14.0 months (95% CI 8.3–20.3) and 8.5 months (95% CI 5.6–16.6) for overall population and patients progressed after a previous VEGFR-TKI, respectively. Median OS was 21.4 months (95% CI 16.0–34.5), confirmed ORR and DCR were 16.7 and 83.3% in overall population. The most common adverse events included diarrhea (47.6%), hypertension (45.2%), hand and foot syndrome (42.9%), and fatigue (40.5%). Grade 3 hematological adverse events occurred in four cases, while no grade 4 hematological adverse events was observed. Conclusions: Anlotinib showed promising efficacy as well as favorable safety as second-line treatment for patients with mRCC. Clinical Trial Registration:www.ClinicalTrials.gov, identifier: NCT02072044.